2016
DOI: 10.1016/j.drugpo.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Harm reduction as a complex adaptive system: A dynamic framework for analyzing Tanzanian policies concerning heroin use

Abstract: Contrary to popular belief, policies on drug use are not always based on scientific evidence or composed in a rational manner. Rather, decisions concerning drug policies reflect the negotiation of actors’ ambitions, values, and facts as they organize in different ways around the perceived problems associated with illicit drug use. Drug policy is thus best represented as a complex adaptive system (CAS) that is dynamic, self-organizing, and coevolving. In this analysis, we use a CAS framework to examine how harm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…These peer organizations have expanded the dissemination of injecting equipment and social practices for safer injection, as well as disseminated knowledge that PWUD can use in everyday life to navigate the contextual pressures that weigh against safer use (including policing, criminalization, stigma, and discrimination) [11, 1419]. However to achieve this, PWUD peer organizations are themselves vulnerable to, and must navigate, tensions between support for harm reduction-based health promotion and the stigmatization, prohibition, and criminalization of drug use which can undermine such support [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…These peer organizations have expanded the dissemination of injecting equipment and social practices for safer injection, as well as disseminated knowledge that PWUD can use in everyday life to navigate the contextual pressures that weigh against safer use (including policing, criminalization, stigma, and discrimination) [11, 1419]. However to achieve this, PWUD peer organizations are themselves vulnerable to, and must navigate, tensions between support for harm reduction-based health promotion and the stigmatization, prohibition, and criminalization of drug use which can undermine such support [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…To understand the problem of addiction, a complex model that involves the interaction of the numerous biopsychosocial variables is required (Griffiths and Larkin, 2004 ; Lewis, 2005 ; Griffiths, 2008 ; Ratliff et al, 2016 ). Similarly, adolescence—as a topic of both research and mental care—involves considering the interaction between multiple factors of varying nature.…”
Section: From Vertebrates To Mammals Towards Homo Sapiens mentioning
confidence: 99%
“…Appendix B gives an overview of risk and protective factors for substance use and prevention interventions for substance use in Africa. A wide spectrum of risk factors were reported in the accepted studies, ranging from age (Crunelle et al, 2018;Cubbins et al, 2012;Sreeramareddy et al, 2014), gender (Birhanu et al, 2014;Cubbins et al, 2012;Medley et al, 2014;Scheibe et al, 2016;Sreeramareddy et al, 2014;Takahashi et al, 2017), level of education (Crunelle et al, 2018), marital status (Cubbins et al, 2012;Sreeramareddy et al, 2014), unemployment (Ratliff et al, 2016;Sreeramareddy et al, 2014), area of residence (Sreeramareddy et al, 2014), occupation (Sreeramareddy et al, 2014), employment status (Cubbins et al, 2012;Sreeramareddy et al, 2014), lack of alcohol use screening (Koopman et al, 2008), poor mental health (Peltzer & Pengpid, 2012;Sfendla et al, 2018), psychological factors (anxiety/stress/depression) (Peltzer & Pengpid, 2012;Sfendla et al, 2018), accessibility of alcohol and substances (Duresso et al, 2018;Embleton et al, 2013;Kalema et al, 2015;Meade et al, 2015;Onya et al, 2012;Scheibe et al, 2016;Takahashi et al, 2017), availability of alcohol and substances (Duresso et al, 2018;Meade et al, 2015;Onya et al, 2012;Takahashi et al, 2017), participants' place of origin (Birhanu et al, 2014;…”
Section: Risk and Protective Factors Identified In The Studiesmentioning
confidence: 99%
“…Additional risk factors reported in East Africa, North Africa as well as in Central Africa were lack of implementation and enforcement of policies (Ali et al, 2012;Ferreira-Borges et al, 2017;Ratliff et al, 2016), lack of refusal skills (Kalema et al, 2015), social pressure (Birhanu et al, 2014;Duresso et al, 2018;Embleton et al, 2013;Takahashi et al, 2017), poor academic performance (Birhanu et al, 2014), addiction (Beard et al, 2010;Embleton et al, 2013), early aggressive behavior (Ghebremichael et al, 2009), sexual abuse (Ghebremichael et al, 2009) as well as women who reported difficulty in conceiving (Ghebremichael et al, 2009). Of particular note is media and advertising (Ferreira-Borges et al, 2017) being reported as a risk factor in Central Africa and lack of inclusion of substance use in the school curricula (Agaku et al, 2015).…”
Section: Risk and Protective Factors Identified In The Studiesmentioning
confidence: 99%